2014
DOI: 10.1007/s40472-014-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Versus Islets After a Successful Kidney Transplant

Abstract: The optimal endocrine transplant that should follow a successful kidney transplant in patients with type 1 diabetes is currently open to debate. Ideally, a combined kidney and pancreas transplant is carried out simultaneously from an optimal donor as there is clear immunological benefit. However, when a living donor kidney transplant occurs initially, either a pancreas after kidney or islet after kidney transplant may be considered. A pancreas after kidney transplant carries more surgical risk but provides mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…More recently, technical failure rates have dropped to 5%, and pancreas allograft survival in PAK has improved, with, respectively, 85% and 60% of patients being insulin-free at one-0year and five years [34]. A PAK exposes the patient to more surgical risk but generally provides higher endocrine reserve compared to the alternative option of IAK transplantation, which is usually proposed for patients considered not fit enough for major surgery [35]. An unresolved aspect of PAK and IAK is optimal timing for the transplant after a successful kidney transplant.…”
Section: Pancreas After Kidney (Pak) Transplant/islet After Kidney (I...mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, technical failure rates have dropped to 5%, and pancreas allograft survival in PAK has improved, with, respectively, 85% and 60% of patients being insulin-free at one-0year and five years [34]. A PAK exposes the patient to more surgical risk but generally provides higher endocrine reserve compared to the alternative option of IAK transplantation, which is usually proposed for patients considered not fit enough for major surgery [35]. An unresolved aspect of PAK and IAK is optimal timing for the transplant after a successful kidney transplant.…”
Section: Pancreas After Kidney (Pak) Transplant/islet After Kidney (I...mentioning
confidence: 99%
“…Xenogeneic islets isolated from pigs is another area of research. Trials of porcine islet xenografts transplanted into primate models have shown a potential to achieve insulin independence and prolonged islet-graft function (>600 days) [34,35]. The disadvantage is that it seems to cause a greater immunological hurdle compared with islet allotransplantation [26,83].…”
Section: Advanced Therapiesmentioning
confidence: 99%